Smoking accelerates renal cystic disease and worsens cardiac phenotype in Pkd1-deficient mice - Marciana V. Sousa (Nature Portfolio, 2021)
Abstract Smoking has been associated with renal disease progression in ADPKD but the underlying deleterious mechanisms and whether it specifically worsens the cardiac phenotype remain unknown. To investigate these matters, Pkd1-deficient cystic mice and noncystic littermates were exposed to smoking from conception to 18 weeks of age and, along with nonexposed controls, were analyzed at 13–18 weeks. Renal cystic index and cyst-lining cell proliferation were higher in cystic mice exposed to smoking than nonexposed cystic animals. Smoking increased serum urea nitrogen in cystic and noncystic mice and independently enhanced tubular cell proliferation and apoptosis. Smoking also increased renal fibrosis, however this effect was much higher in cystic than in noncystic animals. Pkd1 deficiency and smoking showed independent and additive effects on reducing renal levels of glutathione. Systolic function and several cardiac structural parameters were also negatively affected by smoking and the Pkd1-deficient status, following independent and additive patterns. Smoking did not increase, however, cardiac apoptosis or fibrosis in cystic and noncystic mice. Notably, smoking promoted a much higher reduction in body weight in Pkd1-deficient than in noncystic animals. Our findings show that smoking aggravated the renal and cardiac phenotypes of Pkd1-deficient cystic mice, suggesting that similar effects may occur in human ADPKD.